Prevalence of and risk factors associated with faecal carriage of CTX-M β-lactamase-producing enterobacteriaceae in rural Thai communities - Ulzii Orshikh Luvsansharav (2018)
Objectives: To determine the prevalence of CTX-M β-lactamase-producing Enterobacteriaceae and to study the risk factors associated with faecal carriage in asymptomatic rural Thai people. Methods: In all, 417 stool samples were obtained from rural Thai people and screened for extended-spectrum β-lactamases (ESBLs) using MacConkey agar supplemented with 2 mg/L cefotaxime. Results were confirmed using cefotaxime and ceftazidime with and without clavulanic acid. The bla CTX-M genes were identified and genotyped using PCR with bacterial DNA samples. Multivariate analysis was performed to investigate risk factors associated with the faecal carriage of CTX-M producers. Results: The prevalence of CTX-M-type ESBL-producing Enterobacteriaceae was 65.7%. The CTX-M-9 group (60.6%) was dominant, followed by the CTX-M-1 group (38.7%). Most of the bacteria were Escherichia coli (85.4%) and Klebsiella pneumoniae (4.7%). Of a total of 234 E. coli strains, 48.7% belonged to phylogenetic group A, 28.6% to group B1, 15.8% to group D and 6.8% to group B2. Most CTX-M producers were susceptible to carbapenems and amikacin, but resistant to tetracycline and gentamicin. In a multivariate logistic regression model, better education status (OR 2.245; 95% CI 1.297-3.884), history of hospitalization (OR 1.643; 95% CI 1.036-2.603) and the use of antibiotics within the last 3 months (OR 1.883; 95% CI 1.221-2.903) were independently associated with faecal carriage. Conclusions: Faecal carriage of CTX-M-type ESBL-producing Enterobacteriaceae among asymptomatic individuals in rural Thailand remains alarmingly high, and previous antibiotic use and a history of hospitalization may contribute to its dissemination. © The Author 2012. Published by Oxford University Press on behalf of the British Society for Antimicrobial Chemotherapy. All rights reserved.